Social networks: a strategy for enhancing project-stakeholder commitment - Nangoli, Sudi; Ahimbisibwe, Arthur; Namagembe, Sheila; Bashir, Hassan (Journal of Strategy and Management, 2013)
The purpose of this paper is to examine the human dimension of project management by establishing the extent to which social networks influence the commitment of project stakeholders. Up to date, project managers still identify inadequate stakeholder commitment to project undertakings as a key antecedent of project failure and so efforts aimed at addressing this challenge are highly valued. The paper therefore explores the use of social networks as one of the possible strategies to enhance project-stakeholder commitment. Design/methodology/approach – The paper adopts a quantitative, cross-sectional study design. Based on responses from 172 project stakeholders who took part in a sample of 92 citizenship projects conducted by major commercial banks in Uganda, hierarchical regression was used to indicate what happens to a model as different predictor variables are introduced The use of specific type of projects minimizes bias in results due to the unique nature of specific projects hence enhances reliability of results. Findings – The results from statistical analysis reveal that social network elements (network transitivity and network degree) are significant predictors of project stakeholder commitment. The results also suggest that network transitivity is a better significant predictor of project-stakeholder commitment than network degree Practical implications – Project-stakeholder commitment has beenwidely studied in relation to project performance and the study makes a number of contributions to the theory and study of projects. First and foremost, the paper studied project social networks and project-stakeholder commitment in citizenship projects in commercial banks in Uganda which is a developing country. The study therefore contributes to an understanding of project social networks and project-stakeholder commitment in citizenship projects of commercial banks in a developing country. The implication of the findings is that it provides a different view point of understanding the aspects that affect project commitment. A lot of focus has been placed on improving project performance in Uganda, but none has specifically focussed on building projectstakeholder commitment through the use of project social networks. Originality/value – Earlier attempts to investigate the impact of social networks on commitment in projects did not study commitment among individuals. Also, no previous empirical study in less developed countries has given special attention to the effect of social networks on project-stakeholder commitment especially in the domain of citizenship projects which have gained a lot of momentum around the globe. The study results indicate that getting concerned with the nature of social networks the project creates and the means it uses to maintain such networks has implications for projectstakeholder commitment.
Keywords: Social networks; Strategy; Stakeholders; Project management; Project-stakeholder commitment